Intimate creativity : Partners in Love and Art - Sarnoff, Irving; Sarnoff, Suzanne (Wisconsin : The University of Wisconsin Press, 2002)
Christo and Jeanne-Claude ; Diller, Elizabeth ; Scofidio, Ricardo ; Jones, Kristin ; Ginzel, Andrew ; Buchen, Bill ; Buchen, Mary ; Robbins, Andrea ; Becher, Max ; LoCurto, Lilla ; Outcault, Bill et al
boek